2015
DOI: 10.1111/eos.12181
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in marginal and internal fits for different metal and alumina infrastructures cemented on implant abutments

Abstract: Cemented crowns are increasingly being used on dental implants instead of on screw-retained prostheses because of the reliability of internal Morse taper implant-abutment connections. However, there is a lack of information on the fit of metal ceramic and premachined alumina infrastructures. Therefore, the aim of this study was to evaluate the marginal and internal fits of different metal and alumina infrastructures cemented on universal post abutments. A total of 45 abutments (6 mm in height and 3.3 mm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…It has been reported that a 100-120-μm-thick cement layer is considered clinically acceptable for good long-term clinical prognosis of the indirect restoration (7,8). Poor internal adaptation can lead to lack of restoration retention and poor resistance form for the tooth-restoration complex (9,10). Therefore, the study of factors that affect marginal and internal adaptation of indirect restorations is critically important in restorative dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a 100-120-μm-thick cement layer is considered clinically acceptable for good long-term clinical prognosis of the indirect restoration (7,8). Poor internal adaptation can lead to lack of restoration retention and poor resistance form for the tooth-restoration complex (9,10). Therefore, the study of factors that affect marginal and internal adaptation of indirect restorations is critically important in restorative dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…However, this system also has some disadvantages. It demands greater accuracy in the preparation of the surgical bed and larger surgical care and there is less versatility with respect to prosthetic components for external hexagon connections [28]. …”
Section: Discussionmentioning
confidence: 99%
“…For G3, the crowns were cleaned with isopropanol in an ultrasonic bath for 5 minutes, and an adhesive was applied (Scotchbond Universal; 3M ESPE). Next, all crowns were cemented (RelyX Ultimate; 3M ESPE) under a 50‐N constant load using a universal test machine (EMIC DL2000; Instron, Norwood, MA) . The excess cement was removed, and crowns were light‐cured for 30 seconds (Valo Cordless; Ultradent, South Jordan, UT).…”
Section: Methodsmentioning
confidence: 99%
“…Next, all crowns were cemented (RelyX Ultimate; 3M ESPE) under a 50-N constant load using a universal test machine (EMIC DL2000; Instron, Norwood, MA). 16 The excess cement was removed, and crowns were light-cured for 30 seconds (Valo Cordless; Ultradent, South Jordan, UT). After 10 minutes, all crowns were immersed in deionized water for 7 days prior to thermal and mechanical cycling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation